2022
DOI: 10.3389/fspas.2022.952486
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of radiation belt flux depletions at geostationary orbit on different solar drivers during intense geomagnetic storms

Abstract: The loss of electron flux of the outer radiation belt has been widely studied in terms of the mechanism that brings in these losses. There are a few studies which have attempted to explain the interplanetary conditions that favor the depletions. As the Sun is the prime cause of any change happening in the magnetosphere, it is important to look at the solar drivers that bring in such changes. In this study, we attempt to understand the effect of solar structures and substructures on the loss of radiation belt h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The first factor is solar wind dynamic pressure. Previous studies have shown that enhanced solar wind pressure can compress the magnetopause and lead to electron flux dropouts (e.g., Onsager et al, 2007;Turner et al, 2012;Yuan and Zong, 2013;Hudson et al, 2014;Gao et al, 2015;Xiang et al, 2016;Gokani et al, 2022). And, magnetospheric compressions can also lead to the anisotropic distributions of ions and electrons, which generate EMIC waves on the dayside (e.g., Anderson and Hamilton, 1993;McCollough et al, 2010;Usanova et al, 2012;Zhang et al, 2016b;Saikin et al, 2016;Xue et al, 2023;Yan et al, 2023) that can cause the loss of relativistic and ultrarelativistic electrons (e.g., Zhang et al, 2016a;Su et al, 2017;Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first factor is solar wind dynamic pressure. Previous studies have shown that enhanced solar wind pressure can compress the magnetopause and lead to electron flux dropouts (e.g., Onsager et al, 2007;Turner et al, 2012;Yuan and Zong, 2013;Hudson et al, 2014;Gao et al, 2015;Xiang et al, 2016;Gokani et al, 2022). And, magnetospheric compressions can also lead to the anisotropic distributions of ions and electrons, which generate EMIC waves on the dayside (e.g., Anderson and Hamilton, 1993;McCollough et al, 2010;Usanova et al, 2012;Zhang et al, 2016b;Saikin et al, 2016;Xue et al, 2023;Yan et al, 2023) that can cause the loss of relativistic and ultrarelativistic electrons (e.g., Zhang et al, 2016a;Su et al, 2017;Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Xiang et al (2018) have showed that the dominant dropout mechanisms at high L * region are often a combination of EMIC wave scattering and outward radial diffusion. At the same time, the solar wind dynamic pressure was up to 9 nPa (not shown), which can compress the magnetospause and lead to the electron flux loss (e.g., Hudson et al, 2014;Gao et al, 2015;Gokani et al, 2022). At ∼ 02:54-03:03 UT on 18 May 2013, Van Allen Probe B was located at duskside and observed some EMIC waves at three bands (H + , He + and O + ) at L * ∼ 4.0 (SI, Supplementary Figure S1).…”
Section: The May 2013 Eventmentioning
confidence: 99%
“…There are two major loss processes driving outer belt electron flux dropouts: electrons are either lost through the magnetopause into the interplanetary space due to the magnetopause shadowing with enhanced outward radial diffusion (Bortnik et al, 2006;Ma et al, 2020), or lost to the upper atmosphere via interacting with various plasma waves (Blum & Breneman, 2020;Drozdov et al, 2022;Lyu et al, 2022;Usanova et al, 2014). Recent statistical studies reported the important impact of high solar wind dynamic pressure (P SW ) and southward interplanetary magnetic field (IMF) B z on producing significant relativistic electron dropouts (Gao et al, 2015;Gokani et al, 2022;Hua et al, 2023;Onsager et al, 2007;Yuan & Zong, 2013). Moreover, Hua et al (2023) suggested that dropouts strongly depend on storm (SYM-H index) and substorm (AE index) conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their results suggested that electron precipitation at energies >30 keV are driven by chorus waves, while the dropouts of relativistic electrons are not caused by precipitation. By examining the characteristics of the energetic electron dropouts under different solar conditions using long term data set of intense storms during the years of 1996-2019, Gokani et al (2022) suggested the more substantial flux decay with stronger solar wind pressure and speed. However, in contrast to previous studies, their results show that it was either northward IMF B z before turning southward or rapidly fluctuating IMF B z are important in producing significant dropouts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a great number of both observational and modeling studies having successfully explained the physical processes during electron flux dropouts in different events (e.g., Bortnik et al., 2006; Drozdov et al., 2019, 2022; George et al., 2022; Kang et al., 2018; Su et al., 2016; Tsurutani et al., 2016; Tu et al., 2014, 2019; Turner, Shprits, et al., 2012; Turner et al., 2014; Xiang et al., 2017; Zhang, Li, Ma, et al., 2016; Zhang, Li, Thorne, et al., 2016), only a limited number of studies systematically investigated the statistical distributions of the outer belt electron flux dropouts and their dependence on energies, various geomagnetic indices, and solar wind parameters. Several studies have demonstrated the important impact of the high solar wind dynamic pressure (P SW ) and southward interplanetary magnetic field (IMF) B z on producing significant electron flux dropouts (e.g., Gao et al., 2015; Gokani et al., 2022; Onsager et al., 2007; Yuan & Zong, 2013). Based on superposed epoch analysis of high‐speed stream (HSS) driven storms, the study by Borovsky and Denton (2010) suggested that magnetopause shadowing could be crucial for relativistic electron dropouts during HSS storms.…”
Section: Introductionmentioning
confidence: 99%